Creating learning and action space in South Africa’s post-apartheid land redistribution program - Kepe, Thembela; Hall, Ruth (Action research (London, England), 2020)
This paper uses the case of South Africa’s latest land redistribution strategy known as the Proactive Land Acquisition Strategy, to explore whether, and how, research can have direct and positive impacts on beneficiaries of land reform. The study is situated within the practice of action research: to explore how it can generate knowledge that can be shared back and forth between stakeholders, as well as how it may ignite changes that the participants desire. The findings are that Proactive Land Acquisition Strategy is not meeting the overall goals land reform. But action research has allowed the beneficiaries to emerge from the process with new knowledge about their rights, as well as what options they have to move forward in their fight for secure land rights and decent livelihoods. We introduce a concept of a ‘learning and action space’ to explain our practice of action research. The paper concludes that action research is a desirable approach for land reform, but while it succeeded in educating beneficiaries, it is only one ingredient in ongoing struggles to challenge power relations among citizens and between citizens and the state.